Finite Element Numerical Simulation and Repair Process of Laser Cladding Repair of Surface Cracks on Mechanical Parts - Shuangyang Yu; Qi Chong; Jianzhu Zhou; Youwen Yang; Hua Li (Micromachines)
This study focuses on the planetary gear reducer and employs ANSYS 13.0 software to perform thermo-mechanical coupled simulations for the laser cladding repair process, aiming to address gear failure caused by cracks. The optimal theoretical repair parameters were determined based on temperature and stress field analyses, and performance testing of the cladding layer was conducted to validate the feasibility of the selected parameters. The results suggest that a laser power of 140 W and a scanning speed of 8 mm/s represent the optimal theoretical parameters for the laser cladding repair of the gear workpiece. Tensile strength tests revealed that the cladding layer’s maximum tensile strength reached 1312.80 MPa, which was 1.22 times higher than that of the substrate material. Additionally, the wear resistance tests indicated that the wear loss of the cladding layer under the optimized parameters reduced from 9.3 mg for the base material to 0.5 mg, demonstrating excellent wear resistance. Thus, the mechanical properties of the cladding layer were significantly enhanced compared to the base material under these theoretical process parameters.